2005
DOI: 10.1016/j.femsle.2005.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and significance ofBacillus cereusandBacillus thuringiensisin ready-to-eat food

Abstract: Among 48,901 samples of ready-to-eat food products at the Danish retail market, 0.5% had counts of Bacillus cereus-like bacteria above 10(4) cfu g(-1). The high counts were most frequently found in starchy, cooked products, but also in fresh cucumbers and tomatoes. Forty randomly selected strains had at least one gene or component involved in human diarrhoeal disease, while emetic toxin was related to only one B. cereus strain. A new observation was that 31 out of the 40 randomly selected B. cereus-like strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
75
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 47 publications
(51 reference statements)
12
75
0
2
Order By: Relevance
“…AlAshmawy et al (1996) reported lower incidence (64%) of samples were contaminated with B. cereus with a mean value of 2.4×10 7 ± 1.5× 10 7 CFU/g which is slightly lower than the mean count of B. cereus that we recorded. Antithetical findings recorded by Rosenquist et al, (2005) as they found that most of the desserts with milk and rice samples (95.1%) contained much lower B. cereus counts (<10 3 CFU/g) than those recorded by us and 3.1% of the samples harbored B. cereus in counts > 10 4 CFU/g. Li et al (2016) reported higher incidences of nhe (100%) and cytK(91.6) and lower incidence of hbl (4.2%) in B. cereus isolates obtained from cooked rice samples.…”
Section: Discussionmentioning
confidence: 55%
“…AlAshmawy et al (1996) reported lower incidence (64%) of samples were contaminated with B. cereus with a mean value of 2.4×10 7 ± 1.5× 10 7 CFU/g which is slightly lower than the mean count of B. cereus that we recorded. Antithetical findings recorded by Rosenquist et al, (2005) as they found that most of the desserts with milk and rice samples (95.1%) contained much lower B. cereus counts (<10 3 CFU/g) than those recorded by us and 3.1% of the samples harbored B. cereus in counts > 10 4 CFU/g. Li et al (2016) reported higher incidences of nhe (100%) and cytK(91.6) and lower incidence of hbl (4.2%) in B. cereus isolates obtained from cooked rice samples.…”
Section: Discussionmentioning
confidence: 55%
“…The bacterium B. thuringiensis has only in one case been associated with food poisoning (15), although the bacterium has the same genetic potential for producing enterotoxins as B. cereus. A recent study in our laboratory has shown that more than half of the isolated B. cereus-like strains from 40 ready-to-eat products at a Danish retail market in fact belonged to B. thuringiensis (22), indicating that this species could be the causative agent of some of the food-borne outbreaks earlier ascribed to B. cereus. Counts of B. thuringiensis above 10 4 CFU g Ϫ1 were found in some fruits and vegetables (22).…”
mentioning
confidence: 95%
“…A recent study in our laboratory has shown that more than half of the isolated B. cereus-like strains from 40 ready-to-eat products at a Danish retail market in fact belonged to B. thuringiensis (22), indicating that this species could be the causative agent of some of the food-borne outbreaks earlier ascribed to B. cereus. Counts of B. thuringiensis above 10 4 CFU g Ϫ1 were found in some fruits and vegetables (22). Whether the high counts originated from natural contaminants or residues of B. thuringiensis insecticides was not shown.…”
mentioning
confidence: 95%
See 2 more Smart Citations